Respuesta :

Answer:

f ( x ) = ( x - 5 ) ² - 20

Step-by-step explanation:

1- Add the same value to both sides

f ( x ) = x ² - 10x + 5

2- Add 25 to the expression

f ( x ) + ? = x ² - 10x + ? + 5

3- Add 25 to the left-hand side

f ( x ) + ? = x ² - 10x + 25 + 5

4- Factor the expression

f ( x ) + 25 = x ² - 10x + 25 + 5

5- Move the constant to the right

f ( x ) + 25 = ( x - 5 ) ² + 5

6- Calculate

f ( x ) = ( x - 5) ² + 5 - 25

It will help me a lot if you count me as brainlist anyways good luck!